(3HZjI GdBed aj JQJjH GdcGed ddeHQOs - (3eLghds
(3ChdgG (B:s
(3hHYO(B: (3GdCOH ef CTQa UfGYI jcJSHgG GdYGbd hEf GdPi LeY GdeYGQa hCMUGgG GdCejQ CHh RcQjG GHf CHj LYaQ hdeG QSNJ ai GdYdhe bOeg s
(3BNQgG (B:s
(3bGd GdCUeYi (B: (3cGf ef OYGA CHj GdeLjH (B: (3Gddge GLYd NjQ Yedi eG bGQH CLdi bGd (B: (3hcGf jbhd ai OYGFg(B: (3Gddge dG JcdfG Edi CfaSfG afYLR , hdG Edi GdfGS afVjY s
(3GdfSNI cJHJ Yf CUd fbd ef CUd cJH SfI (B646s
(3hGdcJGH eQJH Ydi Gdafhf hebSe Ydi GQHYjf HGHGHBNQ GdfSNI ebGHdI SfI (B1284s
(3ai cTa GdXfhf (B1/247 (3HZjI GdBed (B/ (3dYHO GdhGMO GdWhGNs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs